Patternmaking for Fashion Design - Armstrong, Hellen Joseph (India : Pearson, 2014)
Basic Approach Renowned for its comprehensive coverage, exceptional illustrations and clear instructions, Patternmaking for Fashion Design offers detailed yet easy-to-understand explanations of the essence of patternmaking. Hinging on a recurring theme that all designs are based on one or more of the three major patternmaking and design principles-dart manipulation, added fullness and contouring-it provides students with all the relevant information necessary to create design patterns with accuracy regardless of their complexity. ome innovative, new information in this book include: Updated with modern, cutting-edge sketches and designs. Ribbing added to the knit section of Chapter 27. More materials on children's wear and swim wear. Knock offs. Fitting corrections Advanced design projects A practical introduction to patternmaking Complete coverage of the three steps of design patterns: dart manipulation, added fullness and contouring. Chapter projects
Includes bibliography index
Keywords: Dart Manipulation; Pants